Systematic Country Diagnostic : The Independent State of Papua New Guinea - World Bank Group (World Bank, Washington, DC, 2018)
This Systematic Country Diagnostic (SCD) identifies the main constraints and opportunities that Papua New Guinea faces in achieving the twin goals of ending extreme poverty and boosting shared prosperity. In line with the World Bank Group’s new country engagement model, the findings of the SCD will provide inputs for the preparation of the Country Partnership Framework, which will outline the WBG’s engagement with Papua New Guinea to achieve the twin goals. This SCD is divided into three parts: setting the scene: the SCD sets the scene by outlining past trends in economic structure and performance, providing a snapshot on the state of service delivery, highlighting key issues of particular relevance for youth and women, and analyzing poverty incidence and inequality; identifying pathways for poverty reduction: second, the SCD looks at the most potent pathways for eradicating poverty and boosting shared prosperity, drawing attention to untapped opportunities and key constraints that must be overcome; and summarizing reform priorities: finally, the SCD identifies priorities for policy and reform to accelerate progress toward the twin goals. This diagnostic exercise was conducted in consultation with national authorities and other stakeholders in Papua New Guinea and is based on the current available body of knowledge.